Nonoxidized MXene Quantum Dots Prepared by Microexplosion Method for Cancer Catalytic Therapy. (24th April 2020) - Li, Xuesong; Liu, Feng; Huang, Dapeng; Xue, Ni; Dang, Yangyang; Zhang, Mengqi; Zhang, Leilei; Li, Bo; Liu, Duo; Wang, Lei; Liu, Hong; Tao, Xutang
Abstract: Nanocatalysts based on Fenton or Fenton‐like reactions for amplification of intracellular oxidative stress has become a frontier research area of tumor precise therapy. However, the major translational challenges are low catalytic efficiency, poor biocompatibility, and even potential toxicities. Here, a Ti‐based material with excellent biocompatibility is proposed for cancer treatment. The nonoxidized MXene‐Ti3 C2 T x quantum dots (NMQDs‐Ti3 C2 T x ) are successfully prepared by a self‐designed microexplosion method. Surprisingly, it has an apparent inhibitory and killing effect on cancer cells, and excellent biocompatibility with normal cells. Moreover, the suppression rate of NMQDs‐Ti3 C2 T x on xenograft tumor models can reach 91.9% without damaging normal tissues. Mechanistically, the Ti 3+ of NMQDs‐Ti3 C2 T x can react with H2 O2 in the tumor microenvironment and high‐efficiently produce excessive toxic hydroxyl radicals to increase tumor microvascular permeability to synergistically kill cancer cells. This work should pave the way for tumor catalytic therapy applications of Ti‐based material as a promising and safer route. Abstract : For nanocatalytic treatment of tumors, a safer strategy is proposed: using titanium‐based materials with good biocompatibility for tumor treatment. The prepared nonoxidized MXene‐Ti3 C2 T x quantum dots show satisfactory antitumor effect, proving the feasibility of this strategy. Although inoculated tumor cells are the fastest‐growing HeLa cells, the tumor suppression rate is 91.9%, without affecting the health of mice.